Effects of Chamomilla recutita (L.) on oral wound healing in rats - Duarte, Carina-Magalhaes-Esteves; Quirino, Maria-Rozelide-Souza; Patrocinio, Monica-Cesar; Anbinder, Ana-Lia [UNESP] (Medicina Oral S L, 2011)
Objectives. The purpose of this study was to evaluate the effect of Chamomilla recutita on the healing of ulcers in rats.Study Design. A 5-mm wound was inflicted on the tongue of 36 rats. Treatment group animals were treated topically with 0.04 mL/day of chamomile ointment, whereas control group animals were not treated. Animals were sacrificed after 3, 7 or 10 days. Semi-quantitative analysis of the degree of inflammation, fibroblast count and wound size was performed, as well as histometric analysis of re-epithelialization and percentage of collagen fibers of the lesion.Results. Animals treated with chamomile showed the best results regarding epithelialization and percentage of collagen fibers after 10 days. As expected, time had a statistically significant effect (p<0.05) on fibroblast count, epithelialization, inflammation and wound size; animals sacrificed at 3 days showed the worst results.Conclusions. Chamomile stimulated re-epithelialization and the formation of collagen fibers after 10 days of treatment; it did not, however, influence inflammation or fibroblast count.
Keywords: Chamomile; wound repair; oral ulcer